A influência dos processos hidrológicos e propriedades físico-hídricas dos solos em microbacias - Oliveira, Alessandra da Silva (2025)
Vegetation cover has a close relationship with the hydrological cycle, influencing the movement of water in different compartments of the system. Forest remnants provide benefits such as erosion control, water quality assurance, flow regulation, groundwater recharge, and nutrient cycling. In view of the significant modification of land use and cover caused by anthropogenic intervention on a global scale, conservation has increasingly focused on the restoration of degraded ecosystems. Understanding how different covers affect the soil’s physic-hydric dynamics is essential on multiple fronts, from sustainable management of water resources and ecosystem conservation to the safe design of hydraulic works and structures. In this context, this thesis aimed to characterize and assess the dynamics of hydrological and soil indicators in areas under forest restoration (RES), Eucalyptus sp. (EUC) and forest remnant (REM), with the goal of understanding the relationships among soil, water and vegetation at distinct stages of forest cover. The research was carried out in two micro-basins (A and B) within the Itupeva River sub-basin, between the municipalities of Aguaí and Espírito Santo do Pinhal (SP). 6 × 8 m plots were established in each cover type and monitored monthly over one year to obtain data on hydrological indicators and soil physical and chemical properties necessary to understand hydric dynamics and identify variations among covers and micro-basins with respect to the investigated aspects. The results indicated that, although micro-basin A is more elongated than B, both exhibit low drainage density, gentle slopes and low relief amplitude, conditions that favor infiltration. Internal precipitation (Pi) accounted for 88 % to 97 % of open-area precipitation (Pa), and surface runoff (ES) remained low under all covers, with no significant differences despite slightly higher volumes in EUC. The difference observed in EUC plots suggests that runoff tends to decrease as the eucalyptus develops. Regarding soil physic-hydric attributes, REM cover exhibited higher moisture and total porosity and lower density, whereas soil under EUC was more compact, with lower moisture and porosity. Seasonality is significantly influenced by soil physical parameters. Infiltration parameters (VIB and K) were directly affected by cover type and seasonality, with higher infiltration rates in REM and RES. Soil water repellency was, for the most part, slight but intensified during the dry season. Mechanical resistance to penetration was lower in the surface layer, regardless of cover. A trend of increasing ES with Pi was also observed, as well as a positive correlation between Pi and soil moisture and a negative correlation between moisture and penetration resistance. In summary, this research underscores how cover type modulates hydrological behavior and soil physico-hydric attributes, highlighting the importance of conservation for the maintenance of ecosystem services.